2016
DOI: 10.5433/1679-0359.2016v37n3p1595
|View full text |Cite
|
Sign up to set email alerts
|

Performance and economic viability of feedlot sheep fed different levels of roughage, concentrate, and water

Abstract: The aim of this study was to evaluate performance and economic viability of producing sheep fed different levels of roughage, concentrate, and water. Forty Santa Inês crossbred sheep with an average initial weight of 18.85 ± 2.80 kg and an average age of 5.0 ± 2.0 months were distributed in a completely randomized design with a 2 × 2 factorial arrangement composed of two proportions of roughage and concentrate (30:70 and 70:30) and two levels of water supply (ad libitum, and 50% restriction), with 10 replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…These mechanisms may stimulate ruminants to ingest water while eating or not to eat when dehydrated. In the current study, water restriction reduced water intake (2.88 and 1.53 kg/day for water intake free and water restriction, respectively (Silva et al, 2016)). Forbes (2007) stated that water is the most important nutrient and that its intake is usually twice as much as the animal's DM intake.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…These mechanisms may stimulate ruminants to ingest water while eating or not to eat when dehydrated. In the current study, water restriction reduced water intake (2.88 and 1.53 kg/day for water intake free and water restriction, respectively (Silva et al, 2016)). Forbes (2007) stated that water is the most important nutrient and that its intake is usually twice as much as the animal's DM intake.…”
Section: Discussionmentioning
confidence: 51%
“…The higher CP intake (113.40 g/day higher proportion of concentrate and 85.75 g/day for low, Silva et al, 2016) resulted in increased weight gain and carcass yield. This increased weight gain is a response to the higher TDN intake (679.91 g/day higher proportion of concentrate and 548.45 g/day for low, Silva et al, 2016), since, as stated by Pereira et al (2015), higher TDN intakes increase microbial protein production. Microbial protein is considered the main source of metabolizable protein (MP) for ruminants (Santos and Mendonça, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small ruminants use water efficiently because of their small size, optimal utilization of ingested water (Araújo, Voltolini, Chizzoti, Turco, & Carvalho, 2010;Kumar, Singh, Kumar, Sahoo, Naqvi, 2016. ), ability to retain water and excrete dry stools and concentrated urine, high tolerance to water stress (Silva, Araújo, Oliveira, Azevedo, & Furtado, 2016), and tolerance to foods with high salt concentrations (Moreno et al, 2015;Castro et al, 2017) and high salinity water (Moura et al, 2016;Yousfi, Marques, Betti, Araus, & Serret, 2016). Potter (1968) reported that the consumption of high salinity water by sheep might increase the osmotic pressure in the rumen, without affecting the ruminal microbiota, and change the heart and respiratory rate of the animals (Duarte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given the demand for potable water by the population living in arid and semi-arid regions and the low precipitation associated with a high evaporation in the recurrent periods of drought that affect these regions, many researchers (ADOGLA-BESSA; AGANGA, 2000;CASAMASSIMA et al, 2008;ALAMER, 2009;SILVA et al, 2016) have sought water supply strategies that increase the efficiency in the use of this essential and limited element for animal production.…”
Section: Introductionmentioning
confidence: 99%